Visual languages and culture of the educational professions - Panciroli, Chiara (img journal, 2019)
An ample literature recognises how images can significantly impact learning processes. Indeed, the visual recalls the possibility to stimulate and activate foreknowledge suited to the learning objects and to develop the capacity to problematise the contents proposed with reference to complex contexts. Thus, in the educational contexts, the image and, generally speaking, visual art represent excellent instruments of transmission, communication and deepening of knowledge, contributing to the definition of a cultural model of professional skills, with particular reference to the educational figures like pedagogists, teachers and educators who operate in social and culture contexts.